Selection of a workpiece clamping system for computer-aided subtractive manufacturing of geometrically complex medical models - Wojnarowska Wiktoria (De Gruyter, 2021)
Physical models of anatomical structures can be made using Additive Manufacturing (AM) or Subtractive Manufacturing (SM). The advantage of subtractive techniques over additive ones is the possibility of maintaining the homogeneity and consistency of the processed material, which is extremely important in the case of medical devices. Currently, a geometrically complex medical model can be made even on a simple, 3-axis CNC machine tool. However, often the semi-finished product must be machined in at least two clamping configurations. The aim of the work is to present the method of fixing a workpiece in the process of subtractive production of geometrically complex medical objects on the example of skull bone prostheses. The paper discusses the use of two clamping systems for machining such models. It presents the process of subtractive production of bone prostheses models fitted to the defect of the skull bone with the use of the proposed methods of fixing the workpiece. The result of the work are two models of the skull bone prosthesis. A more complex model was analysed in terms of the accuracy of geometry reproduction. The research confirmed the usefulness of the proposed clamping systems for the preparation of medical models of geometrically complex anatomical structures.